2009
DOI: 10.3329/jhpn.v27i4.3391
|View full text |Cite
|
Sign up to set email alerts
|

Paramedic-conducted Mental Health Counselling for Abused Women in Rural Bangladesh: An Evaluation from the Perspective of Participants

Abstract: This paper reports on evaluation of an initiative to use paramedics as the first-level mental health counsellors of abused women in rural Bangladesh (2003–2004) from the perspective of the abused women who participated in one or more counselling sessions. Thirty in-depth interviews, followed by a survey (n=372), targeted to cover all participants, were conducted in 2006. Overall, the arrangement, management of ethical issues, and skills of paramedics were rated favourably. Most (89%) abused women (n=372) consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 38 publications
(24 reference statements)
0
34
0
Order By: Relevance
“…Therefore, possible effects of dowry demands and/or microfinance plans on IPV are not explored here. Nonetheless, a recent study reports that dowry is uncommon among educated women in Bangladesh 31. Other mechanisms linking microfinance with IPV are more likely to explain these association patterns.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, possible effects of dowry demands and/or microfinance plans on IPV are not explored here. Nonetheless, a recent study reports that dowry is uncommon among educated women in Bangladesh 31. Other mechanisms linking microfinance with IPV are more likely to explain these association patterns.…”
Section: Discussionmentioning
confidence: 95%
“…Programs incorporating mental health into primary care are rare in South Asia. However, one study [50] details an intervention where counseling is integrated into women's health services and finds that women are not only receptive to the counseling, but that the counseling is effective in reducing emotional distress.…”
Section: Discussionmentioning
confidence: 99%
“…Female paramedics received training on data collection regarding violence against women and emotional distress, and they conducted the interviews in private upon receipt of informed consent. As described in a previous paper by Naved et al [36] a woman who reported physical or sexual violence or suicidal ideation or attempt was offered mental health counselling. Strict confidentiality of each participant’s information was maintained while handling the data.…”
Section: Methodsmentioning
confidence: 99%